2016
DOI: 10.1645/15-763
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat Differences in the Benthic Substrata Affect Parasitism in a Pulmonate Snail Host, Helisoma anceps

Abstract: The microhabitats in which hosts live can potentially influence the ability and success of parasites in finding and infecting these hosts. The infection dynamics of both digenetic trematode parasites and a nematode parasite (Daubaylia potomaca) infecting a pulmonate snail, Helisoma anceps , were observed in a small North Carolina lake using 3 different classifications of substratum type based on percent coverage by leaves and debris. There were no differences in snail site occupancy or density between substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The differences in the cercarial prevalence among the three habitat types surveyed may be due to various possible reasons. Although environmental factors were not measured in this study, parameters such as water temperature (Studer and Poulin, 2013), pH (Candia et al, 2015), vegetation cover (Koprivnikar et al, 2007), and leaf litter (Luth et al, 2016) were found to influence snail community and trematode prevalence in an area. It is also important to note that the presence of other animals that may serve as final hosts for these trematodes may also be one reason for prevalence of infection.…”
Section: Resultsmentioning
confidence: 82%
“…The differences in the cercarial prevalence among the three habitat types surveyed may be due to various possible reasons. Although environmental factors were not measured in this study, parameters such as water temperature (Studer and Poulin, 2013), pH (Candia et al, 2015), vegetation cover (Koprivnikar et al, 2007), and leaf litter (Luth et al, 2016) were found to influence snail community and trematode prevalence in an area. It is also important to note that the presence of other animals that may serve as final hosts for these trematodes may also be one reason for prevalence of infection.…”
Section: Resultsmentioning
confidence: 82%
“…The survey results demonstrated that infection in snails and amphibians differed among ponds, and that high prevalence in snails predictably corresponded to increased infection in larval green frogs. The enclosure experiment similarly showed that echinostome abundance in tadpoles differed among ponds and also among sites within ponds, with a non-significant trend of higher abundance in enclosures in structured microhabitats, likely due to higher snail densities in those areas or microhabitat variation in infection in snails (Sapp and Esch, 1994;Zimmermann et al 2016). Structured microhabitats are typically preferred by larval frogs, likely because of protection from some predators and higher resource levels (Warkentin, 1992;Tarr and Babbitt, 2002), but parasitism may introduce a potential cost.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, microplastics could act as a structural barrier to cercaria movement, increasing the time it takes cercariae to contact hosts. If microplastics were to delay cercariae from contacting hosts during their infective period, they could reduce cercarial transmission, as has been documented with other structural barriers (e.g., leaf litter; Zimmermann et al 2016). Given the diversity of host species that trematodes utilize (e.g., humans, fish, mammals, birds, gastropods, reptiles, and amphibians; Fried and Graczyk 2000), the commonality of free-living life stages across trematode species, and the energetic constraints facing them (Fried and Graczyk 1997), understanding the impact of microplastic contamination on trematode cercariae and their transmission to hosts has broad relevance to host-parasite dynamics.…”
Section: Introductionmentioning
confidence: 92%